THE EFFECT OF IMPLEMENTING THE POP-UP BOOK MEDIA-ASSISTED DEMONSTRATION METHOD ON STUDENT RETENTION AND COGNITIVE LEARNING OUTCOMES - Suyatni, Liza; Mubarak, Syarifatul; Riyandari, Baiq Amelia (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2023)
This research aims to determine the effect of applying the demonstration method assisted by pop-up book media on student retention and cognitive learning outcomes. This research was carried out at SMAN 1 Praya Tengah. The research method used was quasi-experimental with a pretest posttest control group design research design. The sampling technique used was purposive sampling. The research sample was students of class X Science consisting of class X Science 2 as the experimental class and X Science 3 as the control class. The instruments used to measure student retention and cognitive learning outcomes are an objective test of 20 questions and a cognitive interference questionnaire. Analysis of retention data and students' cognitive learning outcomes using the independent sample t-test formula obtained a significance value for cognitive retention of 0.00 < 0.005 with the average value obtained by the experimental class being 86.70% and the control class being 72.75%. For cognitive learning outcomes, the significance value was 0.042 <0.005, with the average score obtained by the experimental class being 73.70 and the control class being 60.36. From these results it can be concluded that there is an influence of the application of the demonstration method assisted by pop-up book media on student retention and cognitive learning outcomes